Glutaminyl cyclase is an enzymatic modifier of the CD47- SIRPα axis and a target for cancer immunotherapy - Logtenberg, Meike E W; Jansen, J H Marco; Raaben, Matthijs; Toebes, Mireille; Franke, Katka; Brandsma, Arianne M; Matlung, Hanke L; Fauster, Astrid; Gomez-Eerland, Raquel; Bakker, Noor A M; van der Schot, Simone; Marijt, Koen A; et al. (Nature medicine, 2019)
Cancer cells can evade immune surveillance through the expression of inhibitory ligands that bind their cognate receptors on immune effector cells. Expression of programmed death ligand 1 in tumor microenvironments is a major immune checkpoint for tumor-specific T cell responses as it binds to programmed cell death protein-1 on activated and dysfunctional T cells . The activity of myeloid cells such as macrophages and neutrophils is likewise regulated by a balance between stimulatory and inhibitory signals. In particular, cell surface expression of the CD47 protein creates a 'don't eat me' signal on tumor cells by binding to SIRPα expressed on myeloid cells . Using a haploid genetic screen, we here identify glutaminyl-peptide cyclotransferase-like protein (QPCTL) as a major component of the CD47-SIRPα checkpoint. Biochemical analysis demonstrates that QPCTL is critical for pyroglutamate formation on CD47 at the SIRPα binding site shortly after biosynthesis. Genetic and pharmacological interference with QPCTL activity enhances antibody-dependent cellular phagocytosis and cellular cytotoxicity of tumor cells. Furthermore, interference with QPCTL expression leads to a major increase in neutrophil-mediated killing of tumor cells in vivo. These data identify QPCTL as a novel target to interfere with the CD47 pathway and thereby augment antibody therapy of cancer.